2010
DOI: 10.1111/j.1708-8208.2008.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation Following Implantation of Titanium Sponge Rods into Humeral Osteotomies in Dogs: A Histological and Histometrical Study

Abstract: The Ti foam exhibited good biocompatibility, and its application resulted in improved maintenance of bone height compared with control sites. The Ti foam in a rod design exhibited bone ingrowth properties suitable for further exploration in other experimental situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
2
29
0
1
Order By: Relevance
“…Moreover, a porous structure may also provide new bone tissue ingrowth abilities and vascularisation [9][10][11][12][13]. Therefore, there has been an increasing interest in the development of biomaterial scaffolds that display a porous structure mimicking that of the human bone in recent years [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a porous structure may also provide new bone tissue ingrowth abilities and vascularisation [9][10][11][12][13]. Therefore, there has been an increasing interest in the development of biomaterial scaffolds that display a porous structure mimicking that of the human bone in recent years [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Amount, size, orientation and interconnectivity of the pores interfere positively with cell behavior. Studies have suggested that porous surface improves osseointegration because it provides a greater area at the implant-bone interface [1][2][3]20,23,36 . Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium scaffolds are already successfully employed in preclinical and clinical studies for bone regeneration [21]. However, the application of MIM remains rather rare compared with other more classical metalworking processes, such as selective electron beam melting [22], 3D fiber (3DF) deposition [23], and the space holder method [24]. MIM allows tailoring of material porosity (and, therefore, the E modulus) by adjusting, for example, the sizes and shapes of metal powder particles [25].…”
Section: Uts (Ucs) Ys (Cys) εF (εC) (µG/g) (%)mentioning
confidence: 99%